Maternal Mortality: Sharing Experience from Nobel Medical College Teaching Hospital - Ghimire, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: To analyse causes of maternal deaths and to identify avoidable factors. Methods: This was a retrospective analysis of maternal deaths, during a period of one year from 15th April, 2011-15th April, 2012, at Nobel Medical College Teaching Hospital, Biratnagar in the Eastern Region of Nepal case files and hospital records being the data sources. All the maternal deaths were recorded. Results: In one year study period, out of a total of 2,754 deliveries, there were 8 maternal deaths giving maternal mortality ratio of 310/100,000 live births. Three of them resulted from an induced abortion mishap and five of them were obstetric deaths. Four of the direct obstetric deaths resulted from complications of pregnancy induced hypertension (PIH) of which one case died due to traumatic post partum hemorrhage postpartum hemorrhage (PPH) as a result of torrential bleeding from extensive vaginal wall tear. One indirect obstetric death occurred in a case of twin pregnancy with severe anemia and congestive cardiac failure. Conclusions: Provision of safe abortion services is still not available to many women despite of legalization of abortion in Nepal. Quality antenatal care services would be helpful in avoiding maternal mortality in many situations by detecting and managing medical complications of pregnancy. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11140 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 33-35